Optimal Topology Formation and Adaptation of Integrated Access and Backhaul Networks - Simsek, Meryem; Narasimha, Murali; Orhan, Oner; Nikopour, Hosein; Mao, Wei; Talwar, Shilpa (Frontiers in Communications and Networks, 2021)
With the increasing densification of cellular networks, it has become exceedingly difficult to provide traditional fiber backhaul access to each cell site, which is especially true for small cell base stations (SBSs). The increasing maturity of millimeter wave (mmWave) communication coupled with multiple-input-multiple-output (MIMO) and beamforming technologies has opened up the possibility of providing high-speed wireless backhaul to such cell sites. The third-generation partnership project (3GPP) is defining an integrated access and backhaul (IAB) architecture for the fifth-generation (5G) cellular networks, in which the same infrastructure and spectral resources are used for both the access and the backhaul. In IAB networks, SBSs, so-called IAB nodes, act either as relay nodes carrying the traffic through multiple hops from a macrocell to an end user and vice versa or as access points to serve user equipments (UEs) in their proximity. To this end, the topology of such IAB networks is essential to enable efficient traffic flow and minimize congestion or increase robustness to backhaul link failure. In this paper, we propose a topology formation algorithm together with methodologies to implement it in real networks and compare it with a standard random sequence approach as well as with an optimal topology obtained using dynamic programming. Our simulation results demonstrate that the proposed algorithm outperforms the random sequence approach by 26% on average in terms of lower bound of the network capacity and is up to 99.7% close to the optimal solution, while being significantly less complex.